2013
DOI: 10.1017/s1368980013000475
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc, vitamin B12 and α-tocopherol are positively and plasma γ-tocopherol is negatively associated with Hb concentration in early pregnancy in north-west Bangladesh

Abstract: Objective: The objective of the current analysis was to explore the association of multiple micronutrients with Hb concentration among pregnant women in a South Asian setting, a topic that has not been adequately explored. Design: Sociodemographic, anthropometric and micronutrient status (plasma ferritin, transferrin receptor, retinol, a-and g-tocopherol, folate, vitamin B 12 , Zn) and Hb concentration were assessed at early pregnancy. Setting: The biochemical sub-study was nested within a double-blind, placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
(48 reference statements)
4
21
2
Order By: Relevance
“…Other possible explanation may be urban-rural difference, as the previous studies in India and Sidama targeted only rural areas. The result of the present study was relatively higher than reports from Eastern Sudan (38 %) [32], Central Sudan (45 %) [17], Malawi (36 %) [33], Vietnam 29 % [34], Bangladesh 14.7 % [35], and Iran 49 % [21]. The reason for this difference probably is due to nutritional regiment; cultural differences in food preparation and feeding habit.…”
Section: Discussioncontrasting
confidence: 74%
“…Other possible explanation may be urban-rural difference, as the previous studies in India and Sidama targeted only rural areas. The result of the present study was relatively higher than reports from Eastern Sudan (38 %) [32], Central Sudan (45 %) [17], Malawi (36 %) [33], Vietnam 29 % [34], Bangladesh 14.7 % [35], and Iran 49 % [21]. The reason for this difference probably is due to nutritional regiment; cultural differences in food preparation and feeding habit.…”
Section: Discussioncontrasting
confidence: 74%
“…Similar findings were reported from Sidama, Southern Ethiopia. [20,21] Like wisely, similar studies conducted in Bangladesh, Pakistan and Turkey [25,30,37] were also supported the finding. This could be reflecting more about the influence of pregnancy is interacted with physiological changes and increased metabolic demands.…”
Section: Discussionsupporting
confidence: 67%
“…The high prevalence of ZD in this study as compared to the similar studies conducted in Addis Ababa, Ethiopia (11.3%) [29], Pakistan (27.8%) [30], Eastern and Central Sudan (38% and 45%) [31,32], Malawi (46%) [33], Iran (29% and 49%) [34,35], Vietnam (29%) [36], Bangladesh (14.7%) [37], and Uruguay (7-14%) [38] might be explained by the high food insecurity in the study setting is leading to lack of access to adequate, safe, and nutritious food which in turn leads to low zinc concentration. Moreover, crops grown locally will have low zinc content and households who depend entirely on locally produced crops will be more likely to develop ZD because of the low zinc contents of the Ethiopian soil.…”
Section: Discussionsupporting
confidence: 45%
“…Yet, when assessing the influence of vitamin B 12 on RBC parameters in the absence of anemia, the available data are inconclusive. Several studies have confirmed the relationship between vitamin B 12 concentration and Hb, MCV, MCH and Hct [42][43][44][45]. However, the majority of studies [46][47][48][49], as well as the recent meta-analysis [50], failed to prove such a relationship.…”
Section: Discussionmentioning
confidence: 98%